Victims of crime and community justice - Williams, Brian, 1953-2007 (Jessica Kingsley Publishers, 2005)
Can a victim's experience really be improved purely by diminishing the rights of offenders and increasing penalties for offending? Writing at a time when the UK is beginning to accept that an offender-led criminal justice system cannot provide direct benefits to the victim of crime, Dr Brian Williams lays bare the assumptions about victims and offenders that currently restrict efficient policy-making. He evaluates proposed solutions, including restorative justice and informal community justice, and draws on evidence and experiences from the UK and around the world to investigate which measure.